Development of Antimicrobial Coatings from Ficus carica Latex for Improving the Quality of Dried Figs - Yesuneh Gizaw; Rocío Casquete; María del Carmen Caballero; María de Guía Córdoba; María José Benito (Foods)
To carry out this work, latex from Ficus carica was obtained for the production of coatings, the characteristics of the produced coatings were analyzed, and their application on dried figs was evaluated. Work was conducted to obtain latex and produce coatings, optimizing the mixture and determining its properties. Additionally, the shelf life of coated fruits was studied. The results showed that the coatings had a milky white color, a thickness between 0.04 mm and 0.09 mm, a moisture content close to 25%, and a water solubility ranging from 80% to 98.73%. The 10% latex coatings showed better elasticity and resistance, being selected for the shelf life study. The optimal formulations selected were 28, 29, and 31, all with 10% latex. These coatings exhibited interesting antimicrobial activities against bacteria Escherichia coli, Staphylococcus aureus, and Salmonella choleraesuis and antifungal activity against Botrytis cinerea, Penicillium expansum, Aspergillus flavus, and Monilinia fructicola. When applied to dried figs, it was observed that the appearance of the figs did not visibly change. Antioxidant activity was highest in batch 28, which also showed less microbiology and lower hardness at 60 days. Thus, coatings not only helped maintain the natural color of the fruits but also preserved their freshness and overall quality for a longer period. This makes them an effective and sustainable solution for the food industry.